“Quel est votre projet ?” L’insertion socioprofessionnelle des usagers dans les CPAS bruxellois - Isabelle Lacourt (Brussels Studies, 2007)
Isabelle Lacourt describes and analyses close up the socio-occupational integration (SOI) work done in several welfare offices (CPAS-OCMWs) in the Brussels-Capital Region. In so doing, she pays particular attention to the schemes that have been set up and the tools and methods that are specific to these offices. She starts by reviewing the history of these welfare offices within local administrations and points out the linkage with the “active welfare state” benchmark. She then shows the concrete impacts that the rising importance of these SOI duties has had on the welfare offices’ internal organisation, to wit, the creation of SOI departments, their connections with basic social services, the ways they function, the specific difficulties inherent in SOI, the need to draw up a plan with each client, and the long-term relationships to which this leads.